Первое дело таксы - Шойнеманн Фрауке (Пауль и Сникерс, детективы на четырех лапах, 2020)
Экземпляры: ф.10 (20210216) / Инвентарный номер: 45653 / Цена: / Авт.знак: Ш 78 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)-44